Exploring pre-service English teachers’ perceptions and practices of critical thinking in Indonesian EFL classrooms - Kuswandaru, Ganang; Prasetya, Willy (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
Critical thinking is essential for success in the 21st century, particularly in language learning. This study explores pre-service English language teachers’ (ELTs) perceptions and practices regarding critical thinking instruction in Indonesia. Through a qualitative case study approach, semi-structured interviews were conducted with two pre-service ELTs from a private university in Yogyakarta. Thematic analysis revealed a rich tapestry of insights into the participants’ understanding of critical thinking, their perceived importance in language learning, and their willingness to integrate critical thinking into their teaching practices. The findings highlight the significance of critical thinking in language acquisition, as it empowers students to analyze complex information, evaluate diverse perspectives, and form informed judgments. Participants emphasized the need for incorporating critical thinking strategies into language teaching to enhance students’ cognitive abilities and facilitate deeper understanding. Nevertheless, the study also identified potential challenges, including the uneven distribution of critical thinking practices across the education system and the need for specialized teacher training to implement critical thinking instruction effectively. The study contributes to understanding pre-service ELTs’ perceptions and practices of critical thinking in Indonesia. It also provides valuable insights for teacher training programs, curriculum development, and future research investigating critical thinking instruction in English language teaching.